P2Y receptor regulation of K2P channels that facilitate K(+) secretion by human mammary epithelial cells - Srisomboon, Yotesawee (Am J Physiol Cell Physiol, 2018)
The objective of this study was to determine the molecular identity of ion channels involved in K(+) secretion by the mammary epithelium and to examine their regulation by purinoceptor agonists. Apical membrane voltage-clamp experiments were performed on human mammary epithelial cells where the basolateral membrane was exposed to the pore-forming antibiotic amphotericin B dissolved in a solution with intracellular-like ionic composition. Addition of the Na(+) channel inhibitor benzamil reduced the basal current, consistent with inhibition of Na(+) uptake across the apical membrane, whereas the K(Ca)3.1 channel blocker TRAM-34 produced an increase in current resulting from inhibition of basal K(+) efflux. Treatment with two-pore potassium (K2P) channel blockers quinidine, bupivacaine and a selective TASK1/TASK3 inhibitor (PK-THPP) all produced concentration-dependent inhibition of apical K(+) efflux. qRT-PCR experiments detected mRNA expression for nine K2P channel subtypes. Western blot analysis of biotinylated apical membranes and confocal immunocytochemistry revealed that at least five K2P subtypes (TWIK1, TREK1, TREK2, TASK1, and TASK3) are expressed in the apical membrane. Apical UTP also increased the current, but pretreatment with the PKC inhibitor GF109203X blocked the response. Similarly, direct activation of PKC with phorbol 12-myristate 13-acetate produced a similar increase in current as observed with UTP. These results support the conclusion that the basal level of K(+) secretion involves constitutive activity of apical K(Ca)3.1 channels and multiple K2P channel subtypes. Apical UTP evoked a transient increase in K(Ca)3.1 channel activity, but over time caused persistent inhibition of K2P channel function leading to an overall decrease in K(+) secretion.